Influence of Work Environment Toward Turnover Intention with Motivation and Job Satisfaction as Intervening Variables in PT. TSA - Ikhwan Tri Wiliyanto; I Ketut Sudiarditha; Corry Yohana (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
This research aims to examine wher work environment influences employee turnover intentions at PT TSA. In addition, this study also examines Job Satisfaction and Motivation as an intervening variable as mediating role toward influence of Work Environment on employee turnover intentions. In some literature found that variable Job Satisfaction and Motivation variables cannot mediate influence of Work Environment on Turnover Intention, refore researchers want to reconfirm it once more.This study uses entire population of 256 workers at PT TSA outlets as respondents. In this study re are 5 (five) hyposes to test direct effect and 2 (two) hyposes to test indirect effect through analysis techniques using Structural Equation Modeling (SEM) with AMOS 22 software. n in mediation test researcher uses Sobel test to test significance of effect of mediation found in research model. results of hyposis testing state that all hyposes made on research model are accePTed.